A randomised controlled trial of repeated filmed social contact on reducing mental illness-related stigma in young adults. (19th December 2016) - Koike, S.; Yamaguchi, S.; Ojio, Y.; Ohta, K.; Shimada, T.; Watanabe, K.; Thornicroft, G.; Ando, S.
Abstract : Aims: Public stigma alters attitudes towards people with mental illness, and is a particular concern for young people since most mental health problems occur in adolescence and young adulthood. However, little is known about the long-term effects of repeated filmed social contact (FSC) on reducing mental health-related stigma among young adults in the general population, compared with self-instructional Internet search (INS) and control interventions. Methods: This study is a parallel-group randomised controlled trial over 12 months conducted in Tokyo, Japan. A total of 259 university students (male n = 150, mean age = 20.0 years, s.d. = 1.2) were recruited from 20 colleges and universities between November 2013 and July 2014, without being provided information about the mental health-related survey or trial. Participants were assigned to one of three groups before completion of the baseline survey (FSC/INS/control = 89/83/87). The FSC group received a computer-based 30-min social contact film with general mental health education and five follow-up web-based FSCs at 2-month intervals. The INS group undertook a 30-min search for mental health-related information with five follow-up web-based reminders for self-instructional searches at 2-month intervals. The control group played PC games and had no follow-up intervention. The main outcome measures were the future (intended behaviour) domain of the Reported and Intended Behaviour Scale at 12 months after the intervention. Analysis was conducted in September 2015. Results: At the 12-month follow-up, 218 participants completed the survey (84.1%, 75:70:73). The FSC group showed the greatest change at the 12-month follow-up (FSC: mean change 2.11 [95% CI 1.49, 2.73], INS: 1.04 [0.29, 1.80], control: 0.71 [0.09, 1.33]; FSC v. INS p = 0.037, FSC v. controls p = 0.004). No adverse events were reported during the follow-up period. Conclusions: FSC was more successful in reducing stigma at 12 months after intervention than INS or control interventions. FSC could be used to reduce stigma in educational lectures and anti-stigma campaigns targeted at young people. Study registration: This study is registered at UMIN-CTR (No. UMIN000012239).